Additive effects of simulated climate changes, elevated CO(2), and nitrogen deposition on grassland diversity - Zavaleta, Erika S. (National Academy of Sciences, 2003)
Biodiversity responses to ongoing climate and atmospheric changes will affect both ecosystem processes and the delivery of ecosystem goods and services. Combined effects of co-occurring global changes on diversity, however, are poorly understood. We examined plant diversity responses in a California annual grassland to manipulations of four global environmental changes, singly and in combination: elevated CO(2), warming, precipitation, and nitrogen deposition. After 3 years, elevated CO(2) and nitrogen deposition each reduced plant diversity, whereas elevated precipitation increased it and warming had no significant effect. Diversity responses to both single and combined global change treatments were driven overwhelmingly by gains and losses of forb species, which make up most of the native plant diversity in California grasslands. Diversity responses across treatments also showed no consistent relationship to net primary production responses, illustrating that the diversity effects of these environmental changes could not be explained simply by changes in productivity. In two- to four-way combinations, simulated global changes did not interact in any of their effects on diversity. Our results show that climate and atmospheric changes can rapidly alter biological diversity, with combined effects that, at least in some settings, are simple, additive combinations of single-factor effects.